Humanities perspectives in peace education : re-engaging the heart of Peace Studies - Johnson, Nicole L; Gandhi, Arun (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"In Humanities Perspectives in Peace Education: Re-Engaging the Heart of Peace Studies, scholar-teachers across a variety of humanities fields explore the content, methods, and pedagogies that are unique to their respective disciplines in contributing to the study of peace and justice. In recent decades, even as peace scholarship has burgeoned, many peace studies texts-including those that purport to be interdisciplinary in nature- have emphasized social science perspectives and, in some cases, have foregone exploration of the role of the humanities altogether in comprehensive peace education. While humanities scholars continue to stake out space for peace scholarship within their fields, no volume has attempted to collect the wisdom of multiple humanities disciplines in order to make the case for their critical role in authentic peace education. Humanities Perspectives in Peace Education addresses that shortcoming in the field of peace studies by exploring the ways in which the humanities are uniquely situated to contribute particular content, knowledge, skills, and values required of comprehensive peace education, scholarship, and activism. These include the development of empathy and understanding, creative vision and imagination, personal and communal transformation toward "the good" in society (such as the pursuit of justice, nonviolence, freedom, and human thriving), and field-specific analytical lenses of their own, among other contributions.
Keywords: Peace -- Study and teaching -- United States.; Education, Humanistic -- United States -- Influence.; Education, Higher -- Social aspects -- United States.; Universities and colleges -- United States -- Sociological aspects.; Curriculum change -- United States.; Education -- Teaching -- Subjects -- Arts & Humanities.; Teaching of a specific subject.; Educational: Arts, general.; Educational: Humanities and social sciences, general.; elektronické knihy; electronic books